Retinal Levels of Amyloid Beta Correlate with Cerebral Levels of Amyloid Beta in Young APPswe/PS1dE9 Transgenic Mice before Onset of Alzheimer's Disease. (24th September 2020) - Mei, Xi; Yang, Mengxiang; Zhu, Lina; Zhou, Qi; Li, Xingxing; Chen, Zhongming; Zou, Chenjun
Abstract : Objectives . Retina abnormalities are related to cognitive disorders in patients with Alzheimer's disease (AD). Retinal amyloid beta (A β ) can be labeled by curcumin. We measured A β content in the cerebrum and retina of APPswe/PS1dE9 (APP) transgenic mice with early age to investigate the correlation between cerebrum and retina. Methods . APP mice and age-matched wild-type mice were investigated every month from age 2 months to 6 months to assess changes in A β content in the retina and cerebrum. At the beginning of each month, mice were fed a curcumin diet (50 mg/kg/day) for 7 consecutive days. The A β levels in the retina and cerebrum were measured by ELISAs. Correlations were identified between retinal and cerebral A β contents using Pearson's correlation. Results . In the absence of curcumin, there was a significant correlation between A β contents in the retina and cerebrum of APP mice (r = 0.7291, P = 0.0014 ). With increasing age, A β -mediated degenerative change in the cerebrum (P < 0.001 in 5 months) and retina (P < 0.01 in 5 months) increased significantly. The inhibitory effect of curcumin on the A β level was significant in the cerebrum (P < 0.001 ) and retina (P < 0.01 ) of older APP mice in the early stage of life. Conclusion . We observed a significant correlation between the A β content in the retina and A β content in the cerebrum of APP mice. Our data suggest an appropriate time to measure retinal A β . Although curcumin can label A β in the retina, it also suppresses A β levels and weakens the degree of correlation between A β in cerebrum and retina tissues.